2007
DOI: 10.1007/s11060-007-9366-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of surgery and radiotherapy on neurocognitive functioning and health-related quality of life in WHO grade I meningioma patients

Abstract: Background Potential treatment-related neurotoxicity and the indolent course of the disease mainly feed the controversy concerning the optimal timing of surgery and radiotherapy in meningioma patients. Object To quantify the additional negative effects of conventional radiotherapy compared to surgery alone on neurocognitive functioning and health-related quality of life (HRQOL) in patients with WHO grade I meningiomas. Methods Neurocognitive functioning and HRQOL (SF36, EORTC-BCM20) were assessed in consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 28 publications
8
78
1
5
Order By: Relevance
“…In that study, there was no association between volume and cognitive functioning [6]. Other studies have reported significant cognitive impairment in meningioma patients either pre- or post- surgery [9, 10], although the average tumor size in both of these studies was much greater than the average size of tumor in our study. Those looking at patients both before and after surgery show mixed findings based on factors such as type of intervention, meningioma size, and patient characteristics [7, 8, 19, 20].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In that study, there was no association between volume and cognitive functioning [6]. Other studies have reported significant cognitive impairment in meningioma patients either pre- or post- surgery [9, 10], although the average tumor size in both of these studies was much greater than the average size of tumor in our study. Those looking at patients both before and after surgery show mixed findings based on factors such as type of intervention, meningioma size, and patient characteristics [7, 8, 19, 20].…”
Section: Discussioncontrasting
confidence: 83%
“…Studies available on cognitive functioning in meningioma have identified cognitive impairment in subjects who are being followed clinically (e.g., as part of a “wait and scan” approach [6], during pre-surgical evaluation [7, 8], or following surgical intervention [9, 10]). Recently, van Nieuwenhuizen et al studied a sample of 21 individuals with radiologically confirmed WHO Grade I supratentorial meningiomas who were followed with a “wait and scan” approach.…”
mentioning
confidence: 99%
“…However, using modern techniques, sparing of normal tissue is possible, and consequently the risk for neurocognitive impairment is very low. It has been demonstrated that radiotherapy following surgery did not have an increase neurocognitive impairment (56). In a subsequent study, it was suggested that neurocognitive deficits could be partly ascribed to the use of antiepileptic drugs and tumor location rather than radiotherapy (13).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…5,6 Several groups have investigated the prognostic significance of baseline HQOL parameters and baseline clinical characteristics for clinical outcome. [7][8][9][10] In these studies, a variety of unspecialized HQOL instruments were used to evaluate global HQOL after meningioma resection. However, it is not sufficient to describe the relationship between meningioma and HQOL in global terms.…”
Section: Introductionmentioning
confidence: 99%